2020
DOI: 10.1097/qmh.0000000000000256
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Hospital Accreditation and Outcomes: The Analysis of Inhospital Mortality From the National Claims Data of the Universal Coverage Scheme in Thailand

Abstract: Background: In Thailand, hospital accreditation (HA) is widely recognized as one of the system tools to promote effective operation of universal health coverage. This nationwide study aims to examine the relationship between accredited statuses of the provincial hospitals and their mortality outcomes. Method: A 5-year retrospective analysis of the Universal Coverage Scheme's claim dataset was conducted, using 1 297 869 inpatient discharges from 76 provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Hospitals treating patients with acute ischemic stroke with rtPA must pass hospital accreditation. The treatment results to be better [12]. It was also found that if the patient had the number of microbleed lesions of more than 10 sites on the MRI brain, the mortality rate was higher [13].…”
Section: Discussionmentioning
confidence: 96%
“…Hospitals treating patients with acute ischemic stroke with rtPA must pass hospital accreditation. The treatment results to be better [12]. It was also found that if the patient had the number of microbleed lesions of more than 10 sites on the MRI brain, the mortality rate was higher [13].…”
Section: Discussionmentioning
confidence: 96%
“…The most recent systematic study discovered a link between accreditation and efficiency, effectiveness, timeliness, and safety [ 32 ]. Meanwhile, other research has shown a connection between accreditation and clinical outcome improvements such as decreased standardized mortality ratios for chronic illnesses [ 66 , 67 ] and other measures of service quality [ 68 ]. However, other studies have shown no correlation between accreditation and clinical outcomes [ 59 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“… 242 Hospital accreditation in Thailand reduced hospital mortality related to stroke and sepsis and significantly increased client volumes. 240 Client satisfaction levels were high in two studies. 233 239 The quality improvement support for private hospitals through the Manyata certification resulted in significant improvements in the overall quality scores of the facilities.…”
Section: Resultsmentioning
confidence: 92%
“…Eleven studies evaluated the impacts of various forms of regulation of health facilities on QoC 232–242. In South Africa, hospital accreditation was associated with improved compliance with quality standards.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation